Evaluasi terhadap Tata Ibadah Kontekstual Gereja Kristen Jawa - Ayub Widhi Rumekso (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2019)
The worship of the people of the Javanese Christian Church cannot be separated from the liturgy. The liturgy gives an introduction, views, and attitudes of the Christian faith to the Javanese Christian Church amid its existence. Throughout the history of the MPD liturgies, the I, II, III, and lectionary variations of the I and II liturgical models have been developed. The process of birth and development of the GKJ liturgy are important elements of research to find an explanation, why GKJ people still have a distance from the realities of life that exist in society. The results found in this study indicate that the GKJ liturgy that has been built has not been placed on the reality of the struggle and hopes of the people amid community and cultural life. The current GKJ's view of the liturgy has a similar meaning to the religious rituals of the people that shape the identity of the people, but there is no critical step capability to build up their worship with praxis so that it can be lived in and have an impact on the lives of the people and the community. Abstrak Peribadahan umat Gereja Kristen Jawa tidak bisa dilepaskan dari liturgi. Liturgi memberikan pengenalan, pandangan, serta sikap iman Kristen kepada umat Gereja Kristen Jawa di tengah keberadaannya. Sepanjang sejarah liturgi GKJ telah dikembangkan model liturgi GKJ formula I, II, III, dan leksionari variasi I dan II. Proses kelahiran dan pengembangan liturgi GKJ merupakan unsur-unsur penting penelitian dalam rangka mencari penjelasan, mengapa umat GKJ masih memiliki jarak dengan kenyataan kehidupan yang ada di tengah masyarakat. Hasil yang ditemukan dalam penelitian ini memperlihatkan bahwa liturgi GKJ yang telah dibangun belum diletakkan pada kenyataan pergumulan dan harapan umat di tengah kehidupan masyarakat dan budayanya. Pandangan GKJ masa kini tentang liturgi memiliki persamaan makna dengan ritual keagamaan masyarakat yang membentuk jatidiri umat, tetapi belum ada kemampuan langkah kritis konkrit untuk membangun tata peribadahannya dengan praksis sehigga dapat dihayati dan memberikan dampak bagi kehidupan umat maupun masyarakatnya.